2022
DOI: 10.1136/wjps-2021-000393
|View full text |Cite
|
Sign up to set email alerts
|

ECMO utilization in infants with congenital diaphragmatic hernia in the USA

Abstract: BackgroundCongenital diaphragmatic hernia (CDH) is a cause of significant morbidity. CDH is the most common neonatal diagnosis requiring extracorporeal membrane oxygenation (ECMO).MethodsWe compared the different characteristics of ECMO and non-ECMO patients with CDH in a case-control study. Data were extracted from the Kids’ Inpatient Database. Records from 2006 to 2016 were used. Patients <28 days of age were selected. CDH infants (n=9217) were stratified based on whether they were treated with ECMO (n=34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Of 17 studies examining insurance status, one from South Korea showed higher ECMO use in patients with NHI versus “medical aid” (164). Of 16 U.S. studies, four found no difference (31, 139, 159, 165), 10 showed greater use in patients with private insurance (vs government insurance) (28, 89, 129, 132, 137, 148, 154, 160, 166) or any insurance (vs uninsured) (167). One obstetric study observed higher ECMO use with government insurance (155), and another showed lower ECMO use in insured patients with COVID-19 (138).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 17 studies examining insurance status, one from South Korea showed higher ECMO use in patients with NHI versus “medical aid” (164). Of 16 U.S. studies, four found no difference (31, 139, 159, 165), 10 showed greater use in patients with private insurance (vs government insurance) (28, 89, 129, 132, 137, 148, 154, 160, 166) or any insurance (vs uninsured) (167). One obstetric study observed higher ECMO use with government insurance (155), and another showed lower ECMO use in insured patients with COVID-19 (138).…”
Section: Resultsmentioning
confidence: 99%
“…Individual-level primary themes were: 1) differential access to care (28, 30, 33, 106, 114, 122, 168, 170), 2) varying clinical presentations (26, 27, 30, 31, 80, 92, 128, 161, 168), 3) different religious/cultural preferences (26, 27, 80, 89, 93, 168), or other unmeasured individual SDoH as confounders (30, 84, 96). Hospital-level mechanisms included: 1) provider-level treatment variation (26, 31, 80, 93, 167, 169) and 2) between-hospital variability in offering ECMO, timing of initiation, organizational structure, experience, and standardized care practices/processes (27, 30, 31, 80, 90, 106, 122, 123, 129–131, 154, 157, 161, 168–173). Specific systemic/structural factors such as legal frameworks, economic systems, and social policies included: 1) healthcare system adequacy (pay-for-performance measures [31, 122], disparate insurance access and quality [28, 32, 106, 128, 167] and, in countries with universal healthcare, need for enhanced systems to serve marginalized communities [30, 110, 114, 117]) and 2) geographic centralization, balancing consolidated expertise, and quality with accessibility of time-critical technology (106, 171–174).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation